High frequency of SPG4 in Taiwanese families with autosomal dominant hereditary spastic paraplegia - Lan, Min-Yu (BMC Neurol, 2014)
BACKGROUND: Hereditary spastic paraplegias (HSPs) are a group of neurodegenerative diseases characterized by progressive spasticity and weakness of the lower limbs. SPG4, SPG3A and SPG31 are the three leading causes of autosomal dominant (AD) HSPs. METHODS: A total of 20 unrelated AD-HSP families were recruited for clinical and genetic assessment. Detection of mutations in SPG4, SPG3A and SPG31 genes was conducted according to a standard protocol. Genotype-phenotype correlations and determinants for disease severity and progression were analyzed. RESULTS: Mutations in the SPG4 gene (SPAST) were detected in 18 (90%) of the AD-HSP families. Mutations in SPG4, SPG3A and SPG31 genes were not detected in the remaining two families. Considerable variations in clinical features were noted, even for mutation carriers from the same family. Mutations causing complete loss of the spastin AAA cassette were associated with earlier onset of disease (20 ± 18 years) compared with those with preservation of partial or total AAA cassette (32 ± 19 years, p = 0.041). For those with SPG4 mutations, disease severity was related to the patients’ current age, and the progression rate of disease was positively correlated with age at onset. CONCLUSIONS: SPG4 accounts for most of the AD-HSP cases in Taiwanese, with a frequency significantly higher than in other populations. SPAST mutations which predict complete loss of the spastin AAA cassette were associated with an earlier onset of disease. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12883-014-0216-x) contains supplementary material, which is available to authorized users.